Kingdom of Lesotho : Sixth Review Under the Three-Year Arrangement Under the Extended Credit Facility. (IMF Staff Country Reports; Country Report ;, 2013)
This paper highlights the Kingdom of Lesotho's Sixth Review Under the Three-Year Arrangement under the Extended Credit Facility. Lesotho has maintained robust economic growth, with moderate inflation. The IMF report shows that economic growth is expected to exceed 4 percent, supported by a recovery in agricultural production, enhanced construction, and mining sector expansion. The reconciliation of treasury accounts has been delayed, largely owing to insufficient collaboration between the treasury and budgetary agencies. To address the problem, the Ministry of Finance issued a circular in June 2013 to enforce reconciliation reporting by all such agencies.